Bee Visitors of Quaresmeira Flowers (Tibouchina granulosa Cogn.) in the Region of Dourados (MS-Brasil) - Brizola-Bonacina, Anna Katia; Arruda, Valeska Marques; Alves-Junior, Valter Vieira; Chaud-Netto, Jose [UNESP]; Polatto, Leandro Pereira [UNESP] (California State University, 2012)
This research was developed in the center-urban area at the city of Dourados (MS), in Tibouchina granulosa trees, a plant popularly known as quaresmeira in Brazil. The floral visitors of this species were recorded in three daily periods: 7 - 8 a.m., 1 - 2 p.m. and 4 - 5 p. m. Bee visitors of those plants were collected with an entomological net when they landed on the flowers. The bees were anesthetized in a closed camera containing etila acetate, conserved in Dietrich ' s fixative and, soon afterwards, transferred to 70% ethyl alcohol for subsequent identification. Almost 300 specimens of Africanized Apis mellifera, Trigona spinipes and Tetragonisca angustula were collected. The presence of these three species of bees in the flowers of T. granulosa suggests that they can be considered the main floral visitors of that vegetal species. T. angustula workers did not visit the flowers of T. granulosa between 7 and 8 a.m., but they were the main floral visitors from 4 to 5 p.m. The workers of T. spinipes presented a very aggressive behavior against the Africanized A. mellifera workers on the quaresmeira flowers, defending the food sources with strength and efficiency and provoking a drastic reduction in the number of honeybee visits between 1 and 2 p.m. Nevertheless, they did not interfere in the opportunistic activity of foraging by T. angustula workers, mainly between 4 and 5 p.m. The most important result of this research was the detection of the Competitive Exclusion Principle between A. mellifera and T. spinipes species in relation to the foraging behavior, when they exploit the floral resources of T. granulosa.
Keywords: Quaresmeira; Tibouchina granulosa; Foraging behavior; Bees; Competitive Exclusion Principle